INFLUENCE OF MYCOTOXINS ON IMMUNE RESPONSES AGAINST SALMONELLA TYPHIMURIUM INFECTION OF BROILER CHICKENS - & ALwan, Jawad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Forty broiler chickens, One - day old were randomly divided into four equal groups:  1st group was immunized with 0.5 ml of whole sonicated salmonella antigens (WSSAgs), protein concentration 1.89 mg/ml. Two dose  two weeks intervals, S/C at 7 days old  and  the  chicks  fed   contaminated diet with  mycotoxins for 7 week,   2nd group was immunized with WSSAgs only and treated  as  1st group,  3rd group fed diet contaminated with  mycotoxins  and 4th group was fed  normal diets and served as control negative group, At 30 days, skin test, phagocytic index and serum levels of antibody titers were done, then 1st ,2nd and 3rd groups were inoculated with  high dose of  virulent S.typhimurium , (1ml containing   1  10 12  CFU/ml ), I/V, and  4th group was inoculated I/V,1ml  sterile normal saline and served as control negative group , all chicks were sacrificed at  3 weeks post infection, it was recorded that mycotoxin suppress the  cellular and  humoral immune responses , phagocytic activity ,in addition to high mortality rate were found in  chicks fed contaminated diet with  and without immunization.